Incorporating Ethnoscience into Contextual English Learning Material Design - Napiah, Napiah; Nur’Aini, Siti; Andris, Dias (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This study investigates the effectiveness of Ethnoscience-based English language materials, which are specifically designed to include cultural knowledge into the process of language acquisition. The study focuses on how two instructional development experts validated these materials, evaluating different pedagogical components with the use of a comprehensive scorecard. The evaluation verifies that the resources are highly aligned with educational requirements, have a well-organized structure, and successfully integrate Ethnoscience principles, guaranteeing a comprehensive linguistic and cultural learning experience. The key findings emphasize the systematic organization, clarity, utilization of practical examples, and incorporation of visual aids, all of which contribute to improved understanding and significance. The materials are renowned for their cultural sensitivity and the utilization of precise, grammatically accurate language, which promotes an all-encompassing and courteous teaching setting. The study asserts that the Ethnoscience-based approach greatly enhances English language teaching, advocating for its ongoing assessment and proposing its potential for wider use in diverse educational settings.